2016
DOI: 10.13066/kspm.2016.11.2.25
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Trunk Muscle Activity According to the Direction of Upper Extremity Lifting using Elastic Band

Abstract: | Abstract |1 )PURPOSE: The purpose of this study was to compare the trunk muscle activity according to the direction of upper extremity lifting using elastic band. METHODS:Thirty three healthy individuals participated in this study. Each subject performed upper extremity lifting using elastic band on two different directions (straight and diagonal). And then we compared the muscle activity of respective trunk muscles of both directions. In order to examine the muscle activity of trunk muscle, we used the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…When the trunk bends forward, the length of the lumbar erector spinal muscle increases, and their strength changes, and leading to muscle activity higher [ 15 ]. Lee et al [ 16 ] reported that when resistance exercise was performed while extending the arm forward, the muscle activity of the lumbar erector spinal muscle increased, which is consistent with the results of the present study. Lee [ 17 ] reported that muscle activity in the neck and shoulder muscles was elevated with increased distance between the work table and the trunk.…”
Section: Discussionsupporting
confidence: 92%
“…When the trunk bends forward, the length of the lumbar erector spinal muscle increases, and their strength changes, and leading to muscle activity higher [ 15 ]. Lee et al [ 16 ] reported that when resistance exercise was performed while extending the arm forward, the muscle activity of the lumbar erector spinal muscle increased, which is consistent with the results of the present study. Lee [ 17 ] reported that muscle activity in the neck and shoulder muscles was elevated with increased distance between the work table and the trunk.…”
Section: Discussionsupporting
confidence: 92%
“…Hodges et al observed that trunk muscles are activated before movement of upper extremities17 ) , and Lehman et al reported that movement of upper extremities are associated with trunk muscle activity18 ) . It has also been reported controlled movements of upper extremities activate trunk muscles19 ) .…”
Section: Discussionmentioning
confidence: 94%
“…Through randomized distribution, 10 subjects were assigned to the experimental group which underwent the elastic band exercise program, and 10 subjects were assigned to the control group undergoing the stretching exercise program. During the experiment, subjects were instructed not to wear high heels and the elastic band and stretching exercise program referenced the exercise program used in Lee et al (2016).…”
Section: Subjectmentioning
confidence: 99%
“…The warm-up exercise was not influenced by the set, while the performance of the elastic band exercise was increased to five times per week (Table 1). The intensity of the elastic band exercise was set according to the evidence provided in a previous study (Lee et al, 2016) conducted on healthy adults, and a blue elastic band was used. …”
Section: ) Elastic Band Exercise Program (Experimental Group)mentioning
confidence: 99%